PENGARUH PEMBERIAN KASGOT PADA MEDIA SAPIH TERHADAP PERTUMBUHAN SEMAI KAYU PUTIH (Melaleuca cajuputi) - Benu, Yakub; Manek, Luisa Moi; Purba, Mahardika Putra; Aryani, Ni Kade Ayu D; Aramak, Fredrik S.; Pobas, Melkianus (Universitas Tanjungpura, 2025)
Cajuput oil plays a pivotal role in the production of various products, particularly essential oils. This growing demand has led to increased exploitation of woody plants, raising concerns about the sustainability of raw material supply. To support the cajuput oil industry, silvicultural interventions such as optimizing planting techniques are essential. The optimal growth of cajuput seedlings is a critical factor in ensuring successful cultivation and consistent production. One alternative to enhance seedling growth is the use of kasgot (maggot residue) as a weaning medium. Kasgot, a by-product of the black soldier fly (Hermetia illucens) larval digestion process, has been recognized for its potential to improve soil and growing media fertility. This study aimed to determine the most effective dosage of kasgot for promoting the growth of Melaleuca cajuputi seedlings. The research was conducted over a two month (January